Emancipatory Urban Greening in the Global South: Interdisciplinary and Intercultural Dialogues and the Role of Traditional and Peasant Peoples and Communities in Brazil - Porto, Marcelo Firpo; Fasanello, Marina Tarnowski; da Rocha, Diogo Ferreira; Palm, Juliano Luis (Frontiers in Sustainable Cities, 2021)
This article discusses theoretical, methodological and political issues related to urban greening in the Global South, as well as emancipatory alternatives to envisioning more inclusive, democratic, sustainable and healthy cities. We sustain that the role of traditional and peasant peoples and communities – including indigenous, quilombolas and others - is strategic for thinking about alternatives and actions aimed at the paradigmatic transition that surpasses the vision of Eurocentric modernity. It generates artificial barriers that divide countryside and cities, society and nature, life and economy, as well as subjects and objects in producing and sharing knowledge. These peoples and communities designates a diversity of social situations that have as a common denominator conditions of existence considered to contrast with “modernity,” situated on the margins of the representations of “development” and “progress” of the hegemonic economic and political powers. Our arguments are empirically based on experiences developed in Brazil with interdisciplinary and intercultural dialogues carried out in recent years. The events called “Meetings of Knowledges” brought together academic groups and different social movements and community organizations involving social struggles and topics such as health, environmental conflicts and justice, food security and sovereignty, agroecology, among others. These meetings intend to enhance intercultural and interdisciplinary interactions between agents working together in different territories with concrete knowledges and experiences. The contents generated by the debates held at these events and their developments depict social experiences that reinforce the underlying hypothesis behind this article: the social struggles involving the interaction between traditional and agricultural populations with urban spaces in the Global South provide important evidence for research agendas about emerging emancipatory processes related to urban greening. In the first part of the text, we analyze the historical, social and epistemological meaning of indigenous, quilombola and peasant peoples in the Brazilian context, analyzing both recent contradictions and threats, as well as their role in the emergence of ongoing emancipatory agendas, including interaction with cities. Finally, we show examples related to social struggles, first of an indigenous ethnic group in the Amazon region, and then in two big Brazilian cities, involving social movements and community organizations that integrate actions for decent housing, sanitation, health care, and food along with the rescue of ancestral knowledge.